COMPETITIVENESS ASSESSMENT CONCEPTS - Nedelcheva, Yulia (Revista Inclusiones, 2020)
The aim of the article is to present concepts for assessing of competitiveness. We take into account the ideas of individual authors, as well as their views on the applicability of each concept. Our idea for systematizing concepts is according to the levels in economy. The results of the article define a diversity of concepts for assessing competitiveness. We accept diversity as consequence of the wide range of definitions of competitiveness. Competitiveness assessment concepts cross thresholds specific to each level of the economy.